REHABILITATION AS A COMPONENT OF PUBLIC POLICY IN THE FIELD OF INFORMATION AND PSYCHOLOGICAL SECURITY - Panchenko , O.; Antonov , V. (Theory and Practice of Public Administration, 2020)
The article sets out the theoretical foundations for the development of an effective state policy for organizing rehabilitation assistance to persons who have suffered mental health damage. On the basis of the axiological approach, the concept of national security is examined, with which the information-psychological component is highlighted as “ensuring the psychological well-being of the individual with minimizing various risk factors for the formation and functioning of an adequate information-orientation basis of subjective-personal relations to the world and himself; adaptive capacity for signs of mental health damage”.Various points of view on the concepts of “rehabilitation” and “habilitation” are analyzed, significant differences in their interpretation are indicated. The author’s vision of these concepts is proposed, based on the definition of information and psychological security: the prevention of the risks of mental losses is habilitation; in case of mental losses, post-factum elimination is rehabilitation.The proposed model for ensuring information-psychological security systematically combines the concepts of rehabilitation-habilitation-compensation-adaptation, and reflects four levels of their organization: biological (implementation algorithm - internal reserves); psychological (implementation algorithm - psychological defense mechanisms) social (implementation algorithm - coping technology); socio-psychological (implementation algorithm - integration (socialization).). Each level is accompanied by a component of the information level.The concept of “information-psychological habilitation” is defined as adaptively developing activity for the formation / inculcation / acquisition of turbulent thinking skills in conditions of intensive risky information factors in order to maintain psychological well-being with appropriate quality of human life.It is emphasized that theoretical studies are presented can serve as the basis for the development of relevant legislative acts.